Hydrothermally fabricated surfactant-free CuxAg1−xS composites with enhanced photocatalytic activity and stability. Issue 18 (12th December 2019) - Ayodhya, Dasari; Veerabhadram, Guttena
ABSTRACT: Here, we report the stable and surfactant-free Cu x Ag1− x S composites as nanorod clusters was fabricated by a simple hydrothermal method for the degradation of pesticides including malathion (MLT), monocrotophos (MCP), and chlorpyrifos (CPS) under ultraviolet (UV) light. The degradation of MLT, MCP, and CPS using Cu0.5 Ag0.5 S were up to 97% after 1 h of UV irradiation. The Cu0.5 Ag0.5 S nanorods displayed enhanced photocatalytic activity and the rate of degradation was higher than that of pure CuS and Ag2 S due to an efficient electron transfer process. The stability and reusability assays indicated that the Cu0.5 Ag0.5 S retained more than 90% of activity after five cycles of use. The photocatalytic mechanism was explored from the obtained results of enhanced photocatalytic activity of Cu x Ag1− x S nanorod clusters.